PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KACANG SANGRAI: STUDI KASUS DI UMKM KACANG SANGRAI SARI PANGAN KECAMATAN NGADIROJO, WONOGIRI - Gunawan, Andi; Pujiani, Dewi; Trisnowati, Juni (Surakarta Management Journal, 2024)
This research aims to determine the influence of product quality, price, and service quality on the decision to purchase oven roasted peanuts among consumers of roasted peanut juice, both partially and simultaneously. The population in this study were consumers of peanut products who had made purchases at the food essence factory in Ngadirojo sub-district, where the exact number is not yet known. Sampling in this research used non-probability sampling with a sample of 100 respondents. The analytical method used is multiple linear regression analysis, t test, f test and coefficient of determination. The results of this research show that in particular, perceptions of product quality, price, and service quality have a positive and significant effect on purchasing decisions. The coefficient of determination shows that 74.5% of the variables of price perception, brand image and product quality influence purchasing decisions. Meanwhile, the remaining 25.5% was influenced by other variables not studied.